2022
DOI: 10.1021/acs.chemmater.2c00226
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Computational Screening and Machine Learning Modeling of Janus 2D III–VI van der Waals Heterostructures for Solar Energy Applications

Abstract: Two-dimensional Janus III−VI monolayers and corresponding van der Waals (vdW) heterostructures present immense application potential in the solar energy conversion areas. In this work, we present material screening and machine learning modeling to accelerate the discovery of promising photocatalytic and photovoltaic candidates in Janus III−VI vdW heterostructures. A comprehensive database with a total of 19926 heterostructures has been proposed according to the high-throughput firstprinciples calculations. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 111 publications
(136 reference statements)
0
27
0
Order By: Relevance
“…Since the first solar cells were developed in the 1950s, 1 the search has continued for solar cell materials with higher power conversion efficiencies (PCEs). [2][3][4][5][6][7][8][9][10] Solar cells can be divided into two categories according to their photoelectric conversion mechanism, namely, conventional solar cells 3,4 and excitonic solar cells (XSCs). 5,[11][12][13][14][15] Conventional solar cells are pn-junction cells fabricated from bulk inorganic semiconductors such as Si, GaAs, and CdTe, 2 which suffer from non-radiative recombination of photogenerated electron-hole pairs, severely limiting their solar energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the first solar cells were developed in the 1950s, 1 the search has continued for solar cell materials with higher power conversion efficiencies (PCEs). [2][3][4][5][6][7][8][9][10] Solar cells can be divided into two categories according to their photoelectric conversion mechanism, namely, conventional solar cells 3,4 and excitonic solar cells (XSCs). 5,[11][12][13][14][15] Conventional solar cells are pn-junction cells fabricated from bulk inorganic semiconductors such as Si, GaAs, and CdTe, 2 which suffer from non-radiative recombination of photogenerated electron-hole pairs, severely limiting their solar energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Experimentally, however, most of the heterojunction solar cells still exhibit efficiencies of less than 12%. [19][20][21] It has been theoretically found that the maximum PCEs of 2D heterojunction solar cells consisting of heterobilayers lie in the range of 10-20%, 5,6,[8][9][10][22][23][24][25][26] with only a few of 2D heterojunction solar cells (e.g., a-AsP/GaN, In 2 STe/Al 2 SSe, GaAs/InAs, HfSe 2 /GeO 2 , TiNF/TiNCl, h-BAs/h-BP, boron pnictide/MoSSe, b-PdTe 2 /MoSe 2 , and b-PdTe 2 /MoTe 2 ) being capable of achieving large PCEs over 20%. [5][6][7][8][9][10]27,28 However, most of the compositing 2D materials have not been experimentally realized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this value of band gap for the SiH/MoSi 2 N 4 heterostructure is a suitable band gap with the best light absorption characteristics. 54 The partial density of states (PDOS) of all atoms in the SiH/MoSi 2 N 4 heterostructure are also plotted in Fig. 2(d).…”
Section: Resultsmentioning
confidence: 99%